1, 2, 3‐Triazoles by Click Chemistry Using Azido Esters as a Precursor. Issue 12 (30th October 2020) - Kumari, Dimple; Banerjee, Shaibal
Abstract: This paper describes synthesis and characterization of new di, tetra, and hexa‐1, 2, 3‐triazoles by Click chemistry using synthesized azido esters as one of the precursors. The synthesized triazoles were subjected to detailed characterizations by FTIR, 1 H NMR, 13 C‐NMR, and HRMS. Thermal stability was also performed by using DSC and TGA. Abstract :